Isolation of novel biflavonoids from Cardiocrinum giganteum seeds and characterization of their antitussive activities. (10th August 2018) - Shou, Jia-Wen; Zhang, Rong-Rong; Wu, Hoi-Yan; Xia, Xue; Nie, Hong; Jiang, Ren-Wang; Shaw, Pang-Chui
Abstract: Ethnopharmacological relevance: Seeds of Cardiocrinum giganteum var. yunnanense (Leichtlin ex Elwes) Stearn (Liliaceae), also known as Doulingzi, have been used as a folk substitute for conventional antitussive herb "Madouling" ( Aristolochia species) to treat chronic bronchitis and pertussis. The active antitussive phytochemicals in C. giganteum seeds are not known. Aim of the study: The present work aims at isolating the active phytochemicals in C. giganteum seeds and confirming their antitussive effects. Materials and methods: Active chemicals were isolated from C. giganteum seeds ethanol extract and identified their structures. Antitussive effects were evaluated with the cough frequency of guinea pigs exposed to citric acid. Electrical stimulation of the superior laryngeal nerve in guinea pigs was performed to differentiate the acting site of potential antitussives. Results: Two racemic biflavonoids (CGY-1 and CGY-2) were isolated from C. giganteum seeds. CGY-1 was identified as ( S )-2″ R, 3″ R - and ( R )-2″ S, 3″ S -dihydro-3″-hydroxyamentoflavone-7- methyl ether, which are new compounds and firstly isolated from C. giganteum seeds. Racemic CGY-2 was identified as (S)-2″ R, 3″ R - and (R)-2″ S, 3″ S -dihydro-3″-hydroxyamentoflavone. Both CGY-1 and CGY-2 could significantly inhibit coughs induced by inhalation of citric acid. Further, they acted on the peripheral reflex pathway to inhibit cough after electrical stimulation of the superior laryngeal nerve in guinea pigs. Conclusions: These chemicals isolated from C. giganteum seeds showed good antitussive effects. The data provide scientific evidence to support the traditional use of C. giganteum seeds as an antitussive herbal medicine. Graphical abstract: